Half of expectant women in Montenegro show iodine deficiency, indicating that supplementation during pregnancy is necessary. Issue 2 (14th August 2022) - Đurović, Dijana; Đorđević, Zorica; Mugoša, Boban; Bajić, Borko; Nikolić‐Kokić, Aleksandra; Miletić, Srđan; Spasić, Snežana
Abstract: Objective: In this study, iodine level in pregnant women of Montenegro and their needs for supplementation were investigated. Methods: A urinary iodine concentration (UIC) study of 326 pregnant women between September and December 2017 in three regions of Montenegro was performed. UIC was related to creatinine (UI/Cr ratio). Results: The median UIC (133 ± 5 μg/L) was indicative of iodine deficiency, as the WHO recommended UIC is 150–249 μg/L. The UI/Cr ratio (160 ± 6 μg/g creatinine) was just above the WHO/UNICEF/IGN recommendation. Approximately 50% of the surveyed women had a lower UIC than that recommended. Conclusion: Iodine deficiency is present in pregnant women in Montenegro. Monitoring the UIC during routine analyses in pregnant women in Montenegro is recommended, along with iodine supplementation for individuals that need it. Synopsis: Half of pregnant women in Montenegro have lower iodine levels than recommended. Iodine measurement in pregnant women and its supplementation when required are necessary.